Effect of wind field below unmanned helicopter on droplet deposition distribution of aerial spraying - Shengde, Chen; Lan, Yubin; Jiyu, Li; Zhiyan, Zhou; Aimin, Liu; Yuedong, Mao (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Wind field is one of the important factors affecting the distribution characteristics of aerial spraying droplet deposition. In order to reveal the impact mechanism of droplet deposition distribution by the wind field below agricultural unmanned helicopter rotor, in this study, the wind field distribution below uniaxial single-rotor electric unmanned helicopter rotor was measured by using a wireless wind speed sensor network measurement system for unmanned helicopter. The effects of wind field in three directions (X, Y, Z) below the rotor on droplet deposition distribution were analyzed with the condition of aerial spraying droplet deposition in rice canopy, and the regression model was established via variance and regression analyses of experiment results. The results showed that, the wind field in Y direction had a significant effect on droplet deposition in effective spray area, the wind field in Z direction had an extremely significant effect on droplet deposition in effective spray area, and the corresponding significance (sig.) values were 0.011 and 0.000. Furthermore, the wind field in Z direction had a significant effect on the penetrability and uniformity of droplet deposition in effective spray area, the corresponding sig. values were 0.025 and 0.011 respectively. The wind speed in Y direction at the edge of effective spray area had a significant effect on droplet drift, the sig. value was 0.021. In addition, the correlation coefficient R of the regression model was 0.869 between droplet deposition in effective spray area and the wind speed in Y and Z directions, and 0.915 between the uniformity of droplet deposition in effective spray area and the maximum wind speed in Z direction. The result revealed the influencing mechanism of the wind field below the rotor of uniaxial single-rotor electric unmanned helicopter on the distribution of aerial spraying droplet deposition. The results can provide guidance for the actual production application of aerial spraying to reduce liquid drift and improve the utilization rate of pesticide.Keywords: uniaxial single-rotor electric unmanned helicopter, aerial spraying, wind field, droplet depositionDOI: 10.3965/j.ijabe.20171003.3078Citation: Chen S D, Lan Y B, Li J Y, Zhou Z Y, Liu A M, Mao Y D. Effect of wind field below unmanned helicopter on droplet deposition distribution of aerial spraying. Int J Agric & Biol Eng, 2017; 10(3): 67–77.